2016
DOI: 10.3892/or.2016.4896
|View full text |Cite
|
Sign up to set email alerts
|

NEK2 regulates stem-like properties and predicts poor prognosis in hepatocellular carcinoma

Abstract: NEK2 has been estimated to play an important role in cancer progression. However, its relevance in hepatocellular carcinoma (HCC) has not yet been explored. Immunohistochemistry revealed NEK2 expression was upregulated in HCC. NEK2-positive hepatocellular carcinoma patients were associated with poor prognosis after surgery compared with NEK2-negative patients based on Kaplan-Meier curves. Deletion of NEK2 reduced self-renewal properties and chemotherapeutic resistance, and decreased the stemness associated gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 49 publications
3
42
0
Order By: Relevance
“…Aberrant activation of Wnt/β-catenin signaling pathway plays an important role in sustaining cancer cell stemness [46]. Consistently, Lin et al reported that the overexpression of NEK2 could enhance self-renewal properties in HCC by activating the Wnt/β-catenin pathway [27]. Moreover, a study by Lai et al suggested that the overexpression of NEK2 could induce cell cycle progression and promote proliferation via the activation of Wnt/β-catenin signaling pathway [25].…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…Aberrant activation of Wnt/β-catenin signaling pathway plays an important role in sustaining cancer cell stemness [46]. Consistently, Lin et al reported that the overexpression of NEK2 could enhance self-renewal properties in HCC by activating the Wnt/β-catenin pathway [27]. Moreover, a study by Lai et al suggested that the overexpression of NEK2 could induce cell cycle progression and promote proliferation via the activation of Wnt/β-catenin signaling pathway [25].…”
Section: Discussionmentioning
confidence: 55%
“…Some studies have suggested that NEK2 is overexpressed in HCC tissues compared with adjacent normal tissues and is associated with poor survival [24][25][26][27][28][29][30][31]. In addition, there is evidence showing that elevated NEK2 expression could enhance stem-like properties, drug resistance, and the progression of HCC [27,28]. However, a study by Fu et al reported that HCC patients with high NEK2 expression had better survival [32].…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations